ANALISIS PENGARUH SUKU BUNGA (BI RATE), JUMLAH UANG BEREDAR DAN EKSPOR TERHADAP INFLASI DI INDONESIA PADA MASA PANDEMI COVID-19 - Ratri, Dwi Ajeng; Munawar, Munawar (Journal of Development Economic and Social Studies, 2022)
The Covid-19 pandemic has caused economic turmoil to become erratic, affecting all aspects of Indonesian people’s lives. Thus, this study aims to determine the effect of the money supply, BI Rate and exports on inflation in Indonesia during the Covid-19 pandemic. This type of research is descriptive quantitative and the data used are secondary data from Bank Indonesia, The Central Bureau of Statistics (BPS), The Ministry of Trade and SEKI-BI. This study used the Error Correction Model (ECM) analysis method. The results of this test indicate that the money supply in short-term has a positive and insignificant effect on inflation, while in the long-term the money supply has a negative and significant effect on inflation. The BI Rate in the short-term has a negative and insignificant effect on inflation, while in the long-term the BI Rate has a positive and significant effect on inflation. Exports in the shirt-term have a positive and insignificant effect on inflation, while in the long-term exports have a positive and significant effect on inflation.